Assessment and Optimization of Coagulation Process in Water Treatment Plant: A Review - Danny Pui Wei Sheng; Muhammad Roil Bilad; Norazanita Shamsuddin (ASEAN Journal of Science and Engineering, 2023)
The rapid growth of the human population, industrialization, and urbanization has threatened the global demand for safe drinking water. Water treatment plant plays a vital role in purifying the raw water for consumer use. The typical water treatment process are coagulation-flocculation, sedimentation, and filtration. Among them, the coagulation-flocculation process is the primary stage in the treatment process. This paper reviews and discusses the optimization strategies of a coagulation-flocculation process to enhance overall treatment efficiency. The working principle of the coagulation-flocculation process is first discussed to understand the treatment process better. Next, the importance of aluminum-based coagulants is addressed as chemical coagulants are one of the key factors that can improve the process. The removals of natural organic matter (NOM) by the coagulation-flocculation process were reviewed as NOM normally contributes to the discoloration of water. The optimization of coagulant dosage was also discussed to depict the consequence of uncontrolled dosage. Finally, dosing control strategies in real-time were discussed, namely direct and indirect dosing control.